Effectiveness of Fetal Medicine Foundation’s Non-Biochemical Risk Calculation Algorithm in Detection of Common Trisomies Screening at 11–13 weeks of Gestation: 12 Years’ Experience in Northern Thailand - Kunanukulwatana C; Tongprasert F; Luewan S; Tongsong T (International Journal of Women's Health, 2025)
Chayanid Kunanukulwatana, Fuanglada Tongprasert, Suchaya Luewan, Theera Tongsong Department of Obstetrics and Gynecology, Faculty of Medicine, Chiang Mai University, Chiang Mai, ThailandCorrespondence: Fuanglada Tongprasert, Department of Obstetrics and Gynecology, Faculty of Medicine, Chiang Mai University, Chiang Mai, 50200, Thailand, Tel +66-53-935552, Email fuanglada.t@cmu.ac.thPurpose: To evaluate the efficacy of first-trimester non-biochemical screening using the Fetal Medicine Foundation (FMF) algorithm in predicting fetal common trisomies (trisomy 21, 18, and 13) in clinical practice.Patients and Methods: Between 2011 and 2023, the non-biochemical screening was routinely performed at 11+0-13+6 weeks’ gestation in 9591 singleton pregnancies at Maharaj Nakorn Chiang Mai Hospital, Thailand. The individual risks for common fetal trisomies were calculated by combining maternal age, history of common trisomies in a previous pregnancy, nuchal translucency thickness, and fetal heart rate using the official FMF algorithm. Women with risk of ≥ 1:250 were classified as high risk. The fetal karyotyping results and pregnancy outcomes were reviewed and analyzed.Results: A total of 8491 complete data sets of singleton pregnancies were analyzed. The incidence of common trisomies was 0.5% (46 cases), including 0.3% (28 cases) of trisomy 21, 0.1% (9 cases) of trisomy 18 and 0.1% (9 cases) of trisomy 13. With a cut-off risk of 1:250, FMF algorithm performance for trisomy 21 screening had a sensitivity of 60.7%, specificity of 97.6%, PPV of 7.7%, NPV of 99.9%, and a false positive rate of 2.4%. The performance for detecting all common trisomies demonstrated a sensitivity of 52.2%, specificity of 97.2%, PPV of 9.2%, NPV of 99.7%, and a false positive rate 2.8%.Conclusion: The first trimester non-biochemical FMF algorithm is sufficiently effective in predicting common trisomies, particularly trisomy 21. This simple approach can be easily implemented in clinical practice, including healthcare facilities that lack access to maternal blood testing services.Keywords: trisomy, down syndrome, prenatal screening, first trimester screening, nuchal translucency